The Role of Village Government in Increasing the Potential of the Village to Become an Independent Village - Iswandi, Nadi (Journal of Humanities, Community Service, and Empowerment, 2024)
This research was conducted to find out the role of the Wuasa Village government, North Lore subdistrict, and Poso Regency in creating a developed and independent village, as well as the factors that influence it. This type of research is descriptive research with a qualitative approach. Data was collected using field observation, interviews, and documentation methods. The results of this research show that the role of the village government in realizing a developed and independent village in Wuasa Village, Lore Utara subdistrict, Poso Regency, is to process the village's potential well. Village officials collaborate with local communities to cultivate existing village potential.